Harnessing community expertise in understanding food insecurity to inform responses in a local government area in Victoria, Australia: a mixed methods photovoice study - Annika Molenaar; Pieta Bucello; Sue Kleve (BMC, 2023)
Abstract Background Local food systems which support affordable, equitable, accessible, and sustainable food are important to enhance food access and reduce food insecurity. Cardinia Shire Council, a local government in Victoria, Australia has developed and endorsed a 'Community Food Strategy' to support their local food system and food security. This study aimed to explore local government community member perspectives regarding food access within their local food environment, and suggested areas to be addressed to better support access. Methods A sequential mixed methods photovoice methodology was implemented. Participants aged over 18 years, who resided in Cardinia Shire, completed an online quantitative survey to explore demographics, food access and food security status and severity (18-item USDA Household Food Security Survey Module). The qualitative photovoice method was used, whereby participants were asked to take photographs that represent their experiences of food access. These photographs were used as prompts in a semi-structured interview Interview data were thematically analysed. Results Seventeen participants completed the study, of which five participants experienced varied severity levels of food insecurity. From the photovoice interviews four themes were developed: 1) Food: a connector to self, people and place, 2) Influencers of food access and triggers for food insecurity, 3) Savvy food literacy skills to support access to food, 4) Consequences of and struggles with food insecurity. Participants suggested recommendations for action to support future food access in their community. Conclusions While food choice is influenced by a range of determinants, the local food environment greatly impacts both food access and food choice. A supportive local food system which promotes inclusion of a community voice, community connectedness, food literacy and physical and economic access to local produce is crucial to support food security.